IMPLEMENTASI PROGRAM BALI BEACH CLEAN UP SEBAGAI CORPORATE SOCIAL RESPONSIBILITY (CSR) OLEH PERUSAHAAN COCA-COLA AMATIL INDONESIA DI PANTAI KUTA BALI - Lasaliesanti, Prita (Universitas Madura, 2019)
Waste has been the biggest problem in the world, especially in Indonesia. It’s been written on Indonesian law number 18 year 2008 about waste has become a national problem, so the management must be done comprehensively from upstream to the downstream in order to provide the economic, health, and environment advantage, and also could change people’s habits. Waste problem was spreaded into all over Indonesia, Including Bali Province, Bali is number one famous island in Indoneisa and the biggest tourism activity in Indonesia. It needs a hardwork from community, government, corporate and institution to solve the waste problem in Bali. Coca-Cola Amatil Indonesia as the biggest food and beverage manufacturer in Indonesia aware about this problem and they build Bali Beach Clean Up as the Corporate Social Responsibility program. Coca-Cola Amatil Indonesia has the initiative to clean up five biggest beach in Bali such as Kuta, Kedonganan, Seminyak, Legian and Jimbaran. This research will see the implementation of the program and see what’s the problems inside the program.